Risk Compounds, Preclinical Toxicity Evaluation, and Potential Mechanisms of Chinese Materia Medica–Induced Cardiotoxicity - Zhou, Jie; Peng, Fu; Cao, Xiaoyu; Xie, Xiaofang; Chen, Dayi; Yang, Lian; Rao, Chaolong; Peng, Cheng; Pan, Xiaoqi (Frontiers in Pharmacology, 2021)
Chinese materia medica (CMM) has been applied for the prevention and treatment of diseases for thousands of years. However, arrhythmia, myocardial ischemia, heart failure, and other cardiac adverse reactions during CMM application were gradually reported. CMM-induced cardiotoxicity has aroused widespread attention. Our review aimed to summarize the risk compounds, preclinical toxicity evaluation, and potential mechanisms of CMM-induced cardiotoxicity. All relevant articles published on the PubMed, Embase, and China National Knowledge Infrastructure (CNKI) databases for the latest twenty years were searched and manually extracted. The risk substances of CMM-induced cardiotoxicity are relatively complex. A single CMM usually contains various risk compounds, and the same risk substance may exist in various CMM. The active and risk substances in CMM may be transformed into each other under different conditions, such as drug dosage, medication methods, and body status. Generally, the risk compounds of CMM-induced cardiotoxicity can be classified into alkaloids, terpenoids, steroids, heavy metals, organic acids, toxic proteins, and peptides. Traditional evaluation methods of chemical drug-induced cardiotoxicity primarily include cardiac function monitoring, endomyocardial biopsy, myocardial zymogram, and biomarker determination. In the preclinical stage, CMM-induced cardiotoxicity should be systematically evaluated at the overall, tissue, cellular, and molecular levels, including cardiac function, histopathology, cytology, myocardial zymogram, and biomarkers. Thanks to the development of systematic biology, the higher specificity and sensitivity of biomarkers, such as genes, proteins, and metabolic small molecules, are gradually applied for evaluating CMM-induced cardiotoxicity. Previous studies on the mechanisms of CMM-induced cardiotoxicity focused on a single drug, monomer or components of CMM. The interaction among ion homeostasis (sodium, potassium, and calcium ions), oxidative damage, mitochondrial injury, apoptosis and autophagy, and metabolic disturbance is involved in CMM-induced cardiotoxicity. Clarification on the risk compounds, preclinical toxicity evaluation, and potential mechanisms of CMM-induced cardiotoxicity must be beneficial to guide new CMM development and post-marketed CMM reevaluation.